Thermally induced martensitic transformation and structural properties in Ni-Ta high-temperature shape memory alloys - Yildiz, Koksal (Springer Heidelberg, 2019)
.The morphological, structural and martensitic phase transformation properties of the binary Ni-Ta high-temperature shape memory alloys depending on the composition via SEM-EDX, XRD and DSC observations have been investigated. It was found that the different Ta contents did not change the high-temperature shape memory behaviors of alloy samples with completed martensitic transformation above 220(degrees)C, but had a dramatic effect on the reverse transformation temperatures (As) and transformation hysteresis (Af-Mf) of alloy samples. As the Ta content of the alloy samples decreased, the As temperatures shifted to high-temperatures (>340(degrees)C, and the Af-Mf values arose to temperatures above 100(degrees)C. However, different Ta contents did not cause considerable changes on the morphological and structural properties of the alloy samples. While a very rare dispersed NiTa2 precipitate phase was observed in the microstructure of the alloy samples with Ta contents above 25 at.%, Ni-rich areas were rarely detected in the microstructure of the alloy sample with Ta content below 25 at.%. In addition, no crack formation was observed in the microstructures of the alloy samples.
Keywords: Strain Gradient; Free-Vibrations; Beams; Ni3Ta